Differential Scanning Calorimetry of Rice Starches - Russell, P.L.; Juliano, Bienvenido O. (Wiley, 1983)
DSC thermograms from 5–135°C of eight rice starches, pretreated with sodium dodecyl benzenesulfonate (DoBS) to remove milled rice proteins, gave gelatinization endotherms with characteristic temperature ranges. Good positive correlations were found between gelatinization temperatures measured by DSC and photometry, and between gelatinization enthalpies and gelatinization temperatures. The enthalpy of the amylose‐lipid endotherm at 90–97°C was less for two DoBS‐prepared rice starches than for the same pronase‐treated starches. The endotherm was absent in waxy starch, and its enthalpy followed the level of lipids extracted by cold water‐saturated butanol (WSB). It was concluded that DoBS treatment removed and replaced some of the starch lipid. Although this DoBS did not form a complex with amylose that was observable by DSC, the adsorbed DoBS was extracted by hot WSB.